Stereotactic body radiotherapy (SBRT) with or without surgery for primary and metastatic liver tumors. Issue 1 (January 2016) - Kirichenko, Alexander; Gayou, Olivier; Parda, David; Kudithipudi, Vijay; Tom, Kusum; Khan, Akhtar; Abrams, Peter; Szramowski, Molly; Oliva, Jose; Monga, Dulabh; Raj, Moses; Thai, Ngoc
Abstract: Objectives: We report single center experience on the outcome and toxicity of SBRT alone or in combination with surgery for inoperable primary and metastatic liver tumors between 2007 and 2014. Patients and methods: Patients with 1–4 hepatic lesions and tumor diameter ≤9 cm received SBRT at 46.8Gy ± 3.7 in 4–6 fractions. The primary end point was local control with at least 6 months of radiographic followup, and secondary end points were toxicity and survival. Results: Eighty-seven assessable patients (114 lesions) completed liver SBRT for hepatoma (39) or isolated metastases (48) with a median followup of 20.3 months (range 1.9–64.1). Fourteen patients underwent liver transplant with SBRT as a bridging treatment or for tumor downsizing. Eight patients completed hepatic resections in combination with planned SBRT for unresectable tumors. Two-year local control was 96% for hepatoma and 93.8% for metastases; it was 100% for lesions ≤4 cm. Two-year overall survival was 82.3% (hepatoma) and 64.3% (metastases). No incidence of grade >2 treatment toxicity was observed. Conclusion: In this retrospective analysis we demonstrate that liver SBRT alone or in combination with surgery is safe and effective for the treatment of isolated inoperable hepatic malignancies and provides excellent local control rates.